2016
DOI: 10.1063/1.4959214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deposition rate on the structure and electron density of evaporated BaSi2 films

Abstract: In order to control the electrical properties of an evaporated BaSi 2 film, which is an emerging candidate for the absorber-layer material of earth-abundant thin-film solar cells, we have investigated the effects of deposition rate on the produced phases, microstructure, and carrier density of the thin films grown by thermal evaporation of BaSi 2. X-ray diffraction results show that a high substrate temperature is necessary for BaSi 2 formation at a high deposition rate, which is discussed from viewpoints of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Intrinsically doped BaSi2 shows n-type conductivity regardless of thin-film growth method. An electron concentration n varies from n ~ 10 16 cm -3 for MBE-grown BaSi2 films [16,50] to n >10 18 cm -3 for sputtered or vacuum-evaporated BaSi2 films [48,51,52]. A first-principles DFT supercell approach revealed that this n-type conductivity arises from Si vacancies [53].…”
Section: Intrinsically Doped N-basi2mentioning
confidence: 99%
“…Intrinsically doped BaSi2 shows n-type conductivity regardless of thin-film growth method. An electron concentration n varies from n ~ 10 16 cm -3 for MBE-grown BaSi2 films [16,50] to n >10 18 cm -3 for sputtered or vacuum-evaporated BaSi2 films [48,51,52]. A first-principles DFT supercell approach revealed that this n-type conductivity arises from Si vacancies [53].…”
Section: Intrinsically Doped N-basi2mentioning
confidence: 99%
“…First, we confirm the reproducibility of this calculation. Table I shows 34,36,37 and by calculation. 35 Terai et al also pointed out such a feature of modes in the measurement of the angle dependencies of polarized Raman spectra of a-axis-oriented undoped BaSi 2 epitaxial films on Si(001).…”
Section: B Calculation Resultsmentioning
confidence: 99%
“…The Raman lines originate from Si tetrahedra with T h symmetry in the lattice of BaSi 2 . In the past, they were assigned based on Si tetrahedra with T d symmetry; 34,36,37 however, we found very recently that T h symmetry is more suitable on the basis of experiments by polarized Raman spectroscopy and by infrared absorption spectroscopy. Besides, the Si-Si distances within each Si tetrahedron are different as in 0.234, 0.237, 0.237, 0.241, 0.248, and 0.248 nm, 57 meaning that T d symmetry is not valid.…”
Section: Effects Of Native Defects On the Raman Spectrummentioning
confidence: 99%
See 2 more Smart Citations